Analisa Tutupan dan Indeks Mortalitas Terumbu Karang di Perairan Pasir Tiga Kelurahan Tanjung Ria Kota Jayapura - Triana Mansye Kubelaborbir (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2021)
Coral reef is one of the important ecosystems that are beneficial for the stability of marine ecological conditions as habitat, spawning ground, feeding ground, shelter for various marine biota, and abrasion protection from wave strikes. Pasir Tiga waters is one of the water bodies in Pasir Tiga, Tanjung Ria, Jayapura city, the Province of Papua is inhabited by a variety of marine biota, one of which is coral reef. Nevertheless, the area is remote from the human residence, fishermen often practice unfriendly fishing activities, so that most coral reef ecosystems are damaged. This study was aimed at knowing the percent cover of live corals and mortality index in Pasir Tiga waters, Tanjung Ria, Jayapura city. It was carried out in August to October 2018. There stations were selected based on the presence of coral reefs and data collections used Line Intercept Transect (LIT) method at the depth of 6 and 9 m with 25 m long transect line. Results found that coral reefs in Pasir Tiga waters have the lowest cover, 3.6%, in station 1, 8.08% in station 2, and the highest, 11.68% in station 3. The coral reefs in all 3 stations are damaged. The mortality index was 0.80 in station 1, 0.44 in station 2, and 0.01 in station 3.Key Words: Coral Cover; Coral’s Mortality Index; Line Intercept Transect; Pasir Tiga; Jayapura City